The roles of incentives and voluntary cooperation for contractual compliance - Simon Gächter; Esther Kessler; Manfred Königstein (Institute for the Study of Labor (IZA), 2011)
Efficiency under contractual incompleteness often requires voluntary cooperation in situations where self-regarding incentives for contractual compliance are present as well. Here we provide a comprehensive experimental analysis based on the gift-exchange game of how explicit and implicit incentives affect cooperation. We first show that there is substantial cooperation under non-incentive compatible contracts. Incentive-compatible contracts induce best-reply effort and crowd out any voluntary cooperation. Further experiments show that this result is robust to two important variables: experiencing Trust contracts without any incentives and implicit incentives coming from repeated interaction. Implicit incentives have a strong positive effect on effort only under non-incentive compatible contracts.
urn:nbn:de:101:1-20110621339
Keywords: C70; C90; 330; principal-agent games; gift-exchange experiments; incomplete contracts; explicit incentives; implicit incentives; repeated games; separability; experiments